Analysis of Arc Emission Spectra of Stainless Steel Electric Arc Furnace Slag Affected by Fluctuating Arc Voltage. Issue 1 (January 2014) - Aula, Matti; Mäkinen, Ari; Fabritius, Timo
Control of chromium oxidation in the electric arc furnace (EAF) is a significant problem in stainless steel production due to variations of the chemical compositions in the EAF charge. One potential method to control chromium oxidation is to analyze the emission spectrum of the electric arc in order to find indicators of rising chromium content in slag. The purpose of this study was to determine if slag composition can be gained by utilizing electric arc emission spectra in the laboratory environment, despite electric arc voltage fluctuations and varying slag composition. The purpose of inducing voltage fluctuation was to simulate changes in the industrial EAF process. The slag samples were obtained from Outokumpu Stainless Oy Tornio Works, and three different arc currents were used. The correlation analysis showed that the emission spectra offer numerous peak ratios with high correlations to the X-ray fluorescence-measured slag CrO x /FeO x and MnO/SiO2 ratios. These ratios are useful in determining if the reduction agents have been depleted in the EAF. The results suggest that analysis of laboratory-scale electric arc emission spectra is suitable for indicating the high CrO x or MnO content of the slag despite the arc fluctuations. Reliable analysis of other slag components was not successful.